Data Literacy in STEM-Based Biology Education: A Systematic Review of Trends and Empirical Studies - Intan Rahma Sari; Murni Ramli; Harlita (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Data literacy is a critical competency in 21st-century STEM-based biology education, enabling students to analyze, interpret, and use data for evidence-based decision-making. However, research on this topic remains fragmented and lacks comprehensive synthesis. This study aimed to examine research trends, distribution patterns, and future directions of data literacy in STEM-based biology education. A Systematic Literature Review (SLR) following the PRISMA 2020 framework was conducted using 52 empirical articles indexed in Scopus from 2015 to 2026. The data were analyzed through thematic and bibliometric approaches using VOSviewer and Biblioshiny (Bibliometrix-R). The results showed a substantial increase in publications between 2022 and 2025. Nevertheless, research distribution remains uneven, characterized by the dominance of developed countries, limited international collaboration, and dispersed contributions across authors, institutions, and journals. Bibliometric findings identified data literacy as the central research theme, closely associated with STEM education and increasingly connected to data science. Thematic evolution revealed a shift from foundational conceptual discussions toward technology-oriented and data-driven approaches. These findings highlight the growing importance of data literacy in biology education and emphasize the need for integrated theoretical frameworks, interdisciplinary collaboration, and the adoption of innovative technologies to support future educational practices and research.